Development of Backend Server Based on REST API Architecture in E-Wallet Transfer System - Muhammad, Irfan Rizq Dzaky; Paputungan, Irving Vitra (Jurnal Sains, Nalar, dan Aplikasi Teknologi Informasi, 2024)
Cash payments are starting to shift towards an electronic or cashless payment system. While the process of transferring balances between ewallet at this time is considered less effective because it requires withdrawal from ewallet and replenishment using banks. This paper presents how to develop a Backend Server based on REST API Architecture using the NestJS framework on a ewallet transfer system. The development uses NestJS framework tools, MySQL database, API testing with Postman, Extreme Programming (XP) development method, and BlackBox Testing method. The result of this research is a server side system for transferring funds between ewallet in the form of a REST API that can be used by frontend and mobile developers.